1990
DOI: 10.1897/1552-8618(1990)9[1019:comibr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Measured Instream Biological Responses With Responses Predicted Using the Ceriodaphnia Dubia Chronic Toxicity Test

Abstract: Instream toxicity was predicted with whole effluent toxicity tests. These results were then compared to the observed instream response of the aquatic community. Forty-three comparisons were conducted in freshwater flowing systems using Ceriodaphnia dubia chronic toxicity test procedures and standardized qualitative sampling of benthic macroinvertebrates. In 88% of the comparisons there was agreement between both measures. These data suggest that the use of effluent toxicity testing results as a regulatory tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 2 publications
6
37
0
1
Order By: Relevance
“…Different kinds of biological surveys, e.g., on fish, invertebrates, and periphyton communities, were used to evaluate the impact on the receiving water and how well the toxicity measured with C. dubia correlated to the health of the community. Generally, a good correlation between the two kinds of measurements was found, confirming, therefore, the validity of the C. dubia test Norberg-King and Mount, 1986;Eagleson et al, 1990).…”
Section: Discussionsupporting
confidence: 63%
“…Different kinds of biological surveys, e.g., on fish, invertebrates, and periphyton communities, were used to evaluate the impact on the receiving water and how well the toxicity measured with C. dubia correlated to the health of the community. Generally, a good correlation between the two kinds of measurements was found, confirming, therefore, the validity of the C. dubia test Norberg-King and Mount, 1986;Eagleson et al, 1990).…”
Section: Discussionsupporting
confidence: 63%
“…Benthic community responses to industrial discharges in rivers have been found to agree well with the results of an aquatic toxicity bioassay with the nektonic Ceriodaphnia dubia (Eagleson et al ., 1990) . Similarly, a reduction in benthic macroinvertebrate abundance, diversity, biomass and number of taxa at copper contaminated sites demonstrated the ecological relevance of toxicity bioassays with Daphnia and Hexagenia conducted at these sites (Malueg et al ., 1984a, b) .…”
Section: Benthic Community Analysessupporting
confidence: 57%
“…These can be used for preliminary diagnoses or to monitor sediment toxicity (see Gray & Pearson, 1982) . In freshwater, for example, certain chironomid species are commonly found to prevail in the vicinity of toxic dischargers, whereas ephemeropterans, plecopterans and trichopterans are typically absent (Winner et al ., 1980 ;Sheehan, 1980 ;Malueg et al ., 1984a, b ;Schloesser, 1988 ;Plafkin et al, 1989 ;Eagleson et al, 1990 ; see also Hellawell, 1986) . The assemblage characteristic of contaminated regions of a marine inlet of the North American Pacific coast is an overabundance of the polychaete Tharyx multifilis and the mollusc Axinopsida serricata along with a notorious scarcity of amphipods ; see also Swartz et al ., 1986) .…”
Section: Benthic Community Analysesmentioning
confidence: 97%
“…The data presented here support such an association and provide empirical and statistical evidence that discharge of pesticide-containing water from rice culture adversely affected the Sacramento-San Joaquin striped bass population. This relationship should not be surprising because extensive work by EPA (1991) and others (Eagleson et al 1990) relating the effects of discharges to receiving waters suggests that the acute effects measured in the discharge from CBD should be indicative of adverse effects on biota in the Sacramento River.…”
Section: Discussionmentioning
confidence: 94%